2019
DOI: 10.1194/jlr.m092742
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic endocannabinoids inversely correlate with the development of diet-induced obesity in male and female mice

Abstract: The endocannabinoid (eCB) system regulates energy homeostasis and is linked to obesity development. However, the exact dynamic and regulation of eCBs in the hypothalamus during obesity progression remain incompletely described and understood. Our study examined the time course of responses in two hypothalamic eCBs, 2-arachidonoylglycerol (2-AG) and arachidonoylethanolamine (AEA), in male and female mice during diet-induced obesity and explored the association of eCB levels with changes in brown adipose tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…In particular, while changes in mEPSC frequency could still be observed after 1 week of HFD in response to mTOR and CB1R blockade (Figure 4C), this was not anymore the case after 4 weeks of HFD (Figure 4E), implying that effects might have been occluded by changes in mTOR and CB1R activity induced by the HFD. Supporting this interpretation, hypothalamic endocannabinoid levels are very high in mice after 1 week of HFD, returning slowly to basal, chow-like levels, after 8 weeks on the diet [53]. Remarkably, we observed that ability of AM251 to increase mEPSC at parvocellular neurons was particularly evident at 1 week of HFD (Figure 4G) and that, for the same time point, inhibitory action of WIN on mEPSC was blunted (Figure 4H).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In particular, while changes in mEPSC frequency could still be observed after 1 week of HFD in response to mTOR and CB1R blockade (Figure 4C), this was not anymore the case after 4 weeks of HFD (Figure 4E), implying that effects might have been occluded by changes in mTOR and CB1R activity induced by the HFD. Supporting this interpretation, hypothalamic endocannabinoid levels are very high in mice after 1 week of HFD, returning slowly to basal, chow-like levels, after 8 weeks on the diet [53]. Remarkably, we observed that ability of AM251 to increase mEPSC at parvocellular neurons was particularly evident at 1 week of HFD (Figure 4G) and that, for the same time point, inhibitory action of WIN on mEPSC was blunted (Figure 4H).…”
Section: Discussionsupporting
confidence: 68%
“…Both hypothalamic mTORC1 and CB1R signaling are known to be altered by HFD feeding [50], [51], [52], [53]. Hence, we wondered if HFD exposure could modify mEPSC frequency and how, in turn, modulation of mEPSC frequency by mTORC1 and CB1R signaling could be altered by obesogenic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Next, 50 μl of the homogenized sample were kept at −20 C for protein quantification, and the remaining 150 μl were mixed with 600 μl ethyl acetate/n-hexane (9:1 v/v) and vortexed for 5 min. After centrifugation (14,000 × g, 5 min, 4 C), the upper layer was collected, evaporated in a nitrogen stream and analysed by HPLC-MS/MS, as described previously (Miralpeix et al, 2019).…”
Section: Endocannabinoid Extraction and Analysismentioning
confidence: 99%
“…HEK-293T cell endocannabinoids were extracted and measured by HPLC-MS/MS, as previously described (Miralpeix et al, 2019), but with some modifications. Briefly, cells were seeded on a six-well plate and transfected with EV-SYFP2, ABHD6-SYFP2, and CPT1C-SYFP2 using FuGENE HD (Promega, Madrid, Spain).…”
Section: Endocannabinoid Extraction and Analysismentioning
confidence: 99%
“…Some studies focusing on the hypothalamus have demonstrated that increased endocannabinoid tone in this region is responsible for synaptic remodeling of excitatory and inhibitory synapses, causing the inhibition of anorexigenic neurons and, consequently, hyperphagia and weight gain [99]. Diet-mediated endocannabinoid changes in this region have also been associated with impaired thermogenesis and leptin response activation as a physiological compensatory response [100]. However, recent studies demonstrated that both enhanced endocannabinoid tone and increased CB1 expression in the hypothalamus are transitory and characteristic only of the early phases of exposure to HFD [100].…”
Section: Endocannabinoid System Physiopathology In Obesity and Food Addictionmentioning
confidence: 99%